REAÇÃO DE MARACUJAZEIRO AMARELO ‘AFRUVEC’ E ‘MAGUARY’ A MELOIDOGYNE SPP. - Garcia, M.j.d.m.; Almeida, A.m.; Wilcken, S.r.s [UNESP]; Fischer, I.h.; Sampaio, A.l. [UNESP]; Jesus, A.m. [UNESP]; Fumis, T. [UNESP] (Instituto Biológico, 2021)
The reaction of the yellow passion-fruit cultivars Afruvec and Maguary to Meloidogyne incognita race 2, M. javanica and M. hapla were studied under greenhouse conditions. Three experiments were conducted with similar methodology. The initial population was 5,000 eggs and juveniles of second-stage newly hatched (J2) of M. incognita, M. javanica or M. hapla. The experimental delineations were entirely randomized, with six replications. The evaluated parameters were: gall and egg mass index, roots fresh weight, nematode populations in roots, reproductions factor (FR) and number of nematodes per gram of root. The Afruvec and Maguary cultivars were resistant to Meloidogyne incognita race 2, M. javanica and M. hapla.

A reação do maracujá amarelo ‘Afruvec’ e ‘Maguary’ aos nematóides de galhas Meloidogyne incognita raça 2, M. javanica e M. hapla foi estudada em experimentos conduzidos separadamente para cada espécie de nematóide, em casa de vegetação. As plantas foram inoculadas com 5.000 ovos e eventuais juvenis infectantes. A avaliação foi realizada 60 dias após a inoculação. Os experimentos seguiram o delineamento inteiramente ao acaso com seis repetições, sendo cada parcela constituída por uma planta em vaso de 2 litros com substrato previamente autoclavado. Os parâmetros analisados foram: índice de galhas, índice de massas de ovos, população final do nematóide no sistema radicular e massa do sistema radicular, fator de reprodução do nematóide (FR = Pf/Pi) e o número total de espécimes por grama de raiz. De acordo com os resultados obtidos tanto o maracujá ‘Afruvec’ como o ‘Maguary’ se mostraram resistentes a M. incognita raça 2, M. javanica e M. hapla.
THE REACTION OF THE YELLOW PASSION-FRUIT CULTIVARS AFRUVEC AND MAGUARY TO MELOIDOGYNE SPP
Keywords: Passiflora edulis f flavicarpa; root-knot nematodes; resistance; Passiflora edulis f flavicarpa; nematóides das galhas; resistência